2022
DOI: 10.1111/jcpe.13714
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic outcomes of customized allogeneic bone block versus autogenous bone block for ridge augmentation: 6 Month results of a randomized controlled clinical trial

Abstract: Aim To evaluate the efficacy of customized allogeneic bone block (CABB) for ridge augmentation compared with autogenous bone block. Materials and Methods Patients (N = 24) in need of ridge augmentation were randomly assigned to one of two treatment modalities: CABBs (CABB group) and autogenous bone blocks (ABB group). The primary outcome of the present study was the horizontal bone gain at 1 mm below the alveolar ridge crest (HBG1). Secondary outcomes were the bone gain at other levels, bone resorption rate, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 107 publications
2
6
0
Order By: Relevance
“…In addition, the ramus of the mandible was already associated with a comparable low donor site morbidity [ 5 ]. This is to the results of others in which no donor site complications besides local swelling episodes were detected [ 8 , 35 ]. For postoperative complications using allogeneic bone block grafts, Chaushu et al reported 12.5% of soft tissue perforations, 80% of incision line opening, and 25% of block exposure.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In addition, the ramus of the mandible was already associated with a comparable low donor site morbidity [ 5 ]. This is to the results of others in which no donor site complications besides local swelling episodes were detected [ 8 , 35 ]. For postoperative complications using allogeneic bone block grafts, Chaushu et al reported 12.5% of soft tissue perforations, 80% of incision line opening, and 25% of block exposure.…”
Section: Discussionsupporting
confidence: 86%
“…The efficacy of processed allogeneic bone is comparable to autogenous bone transplants [ 8 , 13 , 31 33 ]. An advantage of the shell technique is the combination of cortical and cancellous bone, as cancellous bone alone seems more vulnerable to bone resorption [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations